2018
DOI: 10.1016/j.hpb.2017.08.016
|View full text |Cite
|
Sign up to set email alerts
|

Utility of drain fluid amylase measurement on the first postoperative day after distal pancreatectomy

Abstract: First postoperative day drain fluid amylase measurement may have a role in excluding pancreatic fistula after distal pancreatectomy. Such patients may be suitable for earlier drain removal.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 45 publications
1
3
0
Order By: Relevance
“…The drain amylase level has also been cited as a risk factor for POPF, although the superiority of drain amylase on POD1 or POD3 is controversial [19–24]. Our data showed that drain amylase levels on POD3 were similarly valuable as a risk factor for POPF to those recorded on POD1 (Table 2).…”
Section: Discussionsupporting
confidence: 51%
“…The drain amylase level has also been cited as a risk factor for POPF, although the superiority of drain amylase on POD1 or POD3 is controversial [19–24]. Our data showed that drain amylase levels on POD3 were similarly valuable as a risk factor for POPF to those recorded on POD1 (Table 2).…”
Section: Discussionsupporting
confidence: 51%
“…This relationship between DFA concentration and salivary fistula development was consistent with research by Larsen et al [6] which showed an upward trend in DFA concentration with early fistulisation. DFA concentration and perioperative albumin ratio has been reported to be an effective predictor of pancreatic fistula development after pancreatomy [7][8][9], also allowing an assessment for the earlier removal of the drain [10]. We speculate that the reason for the association between DFA concentration and salivary fistula development may be as follows.…”
Section: Discussionmentioning
confidence: 86%
“…A meta-analysis and several large-cohort studies have proven that drain fluid amylase on the first postoperative day is a good predictor of development of pancreatic fistula [ 16 18 ]. The results of this study showed that the AUC of the amylase level in the drainage fluid on the first postoperative day for predicting POPF was as high as 0.885, with a sensitivity and specificity of 90% and 81.38%, respectively.…”
Section: Discussionmentioning
confidence: 99%